Pollen, anther, stamen, and androecium mimicry - Lunau, K.; De Camargo, M. G.G. [UNESP]; Brito, V. L.G. (Wiley, 2024)
Floral colours represent a highly diverse communication signal mainly involved in flower visitors' attraction and guidance, but also flower discrimination, filtering non-pollinators and discouraging floral antagonists. The divergent visual systems and colour preferences of flower visitors, as well as the necessity of cues for flower detection and discrimination, foster the diversity of floral colours and colour patterns. Despite the bewildering diversity of floral colour patterns, a recurrent component is a yellow UV-absorbing floral centre, and it is still not clear why this pattern is so frequent in angiosperms. The pollen, anther, stamen, and androecium mimicry (PASAM) hypothesis suggests that the system composed of the flowers possessing such yellow UV-absorbing floral reproductive structures, the flowers displaying central yellow UV-absorbing structures as floral guides, and the pollen-collecting, as well as pollen-eating, flower visitors responding to such signals constitute the world's most speciose mimicry system. In this review, we call the attention of researchers to some hypothetical PASAM systems around the globe, presenting some fascinating examples that illustrate their huge diversity. We will also present new and published data on pollen-eating and pollen-collecting pollinators' responses to PASAM structures supporting the PASAM hypothesis and will discuss how widespread these systems are around the globe. Ultimately, our goal is to promote the idea that PASAM is a plausible first approach to understanding floral colour patterns in angiosperms.
Keywords: anther mimicry; floral colour pattern; floral guide; pollen mimicry; stamen mimicry